Selected endocrine disrupting compounds (vinclozolin, flutamide, ketoconazole and dicofol): effects on survival, occurrence of males, growth, molting and reproduction of Daphnia magna - Haeba, Maher H; Hilscherová, Klára; Mazurová, Edita; Bláha, Ludek (Environmental science and pollution research international, 2008)
BACKGROUND, AIM AND SCOPE: Pollution-induced endocrine disruption in vertebrates and invertebrates is a worldwide environmental problem, but relatively little is known about effects of endocrine disrupting compounds (EDCs) in planktonic crustaceans (including Daphnia magna). Aims of the present study were to investigate acute 48 h toxicity and sub-chronic (4-6 days) and chronic (21 days) effects of selected EDCs in D. magna. We have investigated both traditional endpoints as well as other parameters such as sex determination, maturation, molting or embryogenesis in order to evaluate the sensitivity and possible use of these endpoints in ecological risk assessment. MATERIALS AND METHODS: We have studied effects of four model EDCs (vinclozolin, flutamide, ketoconazole and dicofol) on D. magna using (i) an acute 48 h immobilization assay, (ii) a sub-chronic, 4-6 day assay evaluating development and the sex ratio of neonates, and (iii) a chronic, 21 day assay studying number of neonates, sex of neonates, molting frequency, day of maturation and the growth of maternal organisms. RESULTS: Acute EC50 values in the 48 h immobilization test were as follows (mg/L): dicofol 0.2, ketoconazole 1.5, flutamide 2.7, vinclozolin >3. Short-term, 4-6 day assays with sublethal concentrations showed that the sex ratio in Daphnia was modulated by vinclozolin (decreased number of neonate males at 1 mg/L) and dicofol (increase in males at 0.1 mg/L). Flutamide (up to 1 mg/L) had no effect on the sex of neonates, but inhibited embryonic development at certain stages during chronic assay, resulting in abortions. Ketoconazole had no significant effects on the studied processes up to 1 mg/L. DISCUSSION: Sex ratio modulations by some chemicals (vinclozolin and dicofol) corresponded to the known action of these compounds in vertebrates (i.e. anti-androgenicity and anti-oestrogenicity, respectively). Our study revealed that some chemicals known to affect steroid-regulated processes in vertebrates can also affect sublethal endpoints (e.g. embryonic sex determination and/or reproduction) in invertebrates such as D. magna. CONCLUSIONS: A series of model vertebrate endocrine disrupters affected various sub-chronic and chronic parameters in D. magna including several endpoints that have not been previously studied in detail (such as sex determination in neonates, embryogenesis, molting and maturation). Evaluations of traditional reproduction parameters (obtained from the 21 day chronic assay). as well as the results from a rapid, 4-6 day, sub-chronic assay provide complementary information on non-lethal effects of suspected organic endocrine disrupters. RECOMMENDATIONS AND PERSPECTIVES: It seems that there are analogies between vertebrates and invertebrates in toxicity mechanisms and in vivo effects of endocrine disruptors. However, general physiological status of organisms may also indirectly affect endpoints that are traditionally considered 'hormone regulated' (especially at higher effective concentrations as observed in this study) and these factors should be carefully considered. Further research of D. magna physiology and comparative studies with various EDCs will help to understand mechanisms of action as well as ecological risks of EDCs in the environment.
Keywords: oxazoly; Flutamide; Daphnia; Animals, Newborn; Reproduction; pohlavní dospělost; poměr pohlaví; flutamid; dikofol; Oxazoles; mužské pohlaví; Dicofol; ketokonazol; novorozená zvířata; endokrinní disruptory; chemické látky znečišťující vodu; Molting; Ketoconazole; Water Pollutants, Chemical; ženské pohlaví; Endocrine Disruptors; Locomotion; zvířata; shazování tělního pokryvu; rozmnožování; Sexual Maturation; Sex Ratio; Female; lokomoce; Male; Animals